PENCEGAHAN COVID-19 BAGI IBU HAMIL : LITERATURE REVIEW - Jane Leo Mangi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) is caused by acute chronic respiratory syndrome coronavirus 2 (SARS-CoV-2). The inflammation of COVID-19 causes severe, moderate, or mild symptoms. The stage in carrying out efforts to avoid the formation of COVID-19 infection is an important target group, namely the grouping that is categorized as high risk, one of which is pregnant women. Currently, the distribution of COVID-19 prevention data for pregnant women is very limited. Objective: This literature review aims to identify the efforts that have been made to prevent the outbreak and spread of COVID-19 in pregnant women during the pandemic era. Methods: The research method is library research that collects and analyzes information on efforts to prevent COVID-19 among pregnant women during the past year during the prevention of the COVID-19 pandemic through the Google Scholar, PubMed, Springer, and Lancet databases. research articles. Take advantage of Covid-19 keywords. Results: prevention, infection, COVID-19, pregnancy. Results: Efforts to prevent COVID-19 include wearing masks, washing hands, maintaining physical distance after vaccination, exercising to stay fit, and eating balanced and nutritious food and lots of vitamins for endurance. Conclusion: Based on the literary studies that have been tried, the problem of COVID-19 in pregnant women can be controlled, but preventive actions must be tried to better regulate the spread of COVID-19.